2015
DOI: 10.1007/s11661-015-3046-6
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous Precipitation in Ni-Base Superalloys During Solution Heat Treatment

Abstract: Discontinuous precipitation in single-crystal Ni-base superalloys during solution heat treatment has been studied. It is found that discontinuous precipitation occurs at temperatures approaching the solvus, where volume diffusion is dominant. Diffusion of Al ahead of the boundary leads to gamma prime precipitation and is accompanied by a loss in the driving force available for advancement of the grain boundary. The rate of gamma prime precipitation was tracked using in situ neutron diffraction during isotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Backscattered electron images (BEI) were collected using a retractable solid-state back-scatter detector using high (20 kV) electron beam accelerating voltages for enhanced compositional contrast. Chemical analysis was undertaken in this system at 20 kV using Energy Dispersive Spectroscopy (EDS) using an Octane super 60 mm 2 Silicon Drift Detector (SDD) from EDAX. The dual beam system was also used to prepare site specific TEM samples using an in-situ lift-out procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Backscattered electron images (BEI) were collected using a retractable solid-state back-scatter detector using high (20 kV) electron beam accelerating voltages for enhanced compositional contrast. Chemical analysis was undertaken in this system at 20 kV using Energy Dispersive Spectroscopy (EDS) using an Octane super 60 mm 2 Silicon Drift Detector (SDD) from EDAX. The dual beam system was also used to prepare site specific TEM samples using an in-situ lift-out procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The natural choice of material for the turbine in aero engine applications are Ni-base superalloys owing to their excellent combination of strength, ductility and high temperature oxidation properties [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…[1,4,5,[26][27][28] This is because an increased cross section of a casting has a wider mushy zone, providing a sufficient reservoir for the interdendritic convection, and the convention favors the freckle formation. [29][30][31][32] In contrast, freckles are normally not found in components with small cross-sectional area. [1] This is commonly referred to as the size effect of freckle formation.…”
Section: DX Ma Zh Dong F Wang and Hb Dongmentioning
confidence: 99%
“…As a result, recent studies revealed that vaporization of Ni, Al and Cr occurs during solution heat treatment, which leads to the formation of various surface defects, such as surface recrystallization, surface scale and melting during manufacturing. [26][27][28] Vaporization-induced surface defects in Ni-base superalloys have become one of the most important challenges in manufacturing single-crystal components. [28][29][30] Due to the important roles of Ni, Al and Cr affecting vaporization during solution heat treatment of Ni-base superalloys revealed by our previous publication, [27,28,31] Ni-Al-Cr alloys were selected for vaporization examination of their thermodynamic properties for simplicity purposes.…”
Section: Ni-base Superalloys Have Been Developed Formentioning
confidence: 99%
“…[26][27][28] Vaporization-induced surface defects in Ni-base superalloys have become one of the most important challenges in manufacturing single-crystal components. [28][29][30] Due to the important roles of Ni, Al and Cr affecting vaporization during solution heat treatment of Ni-base superalloys revealed by our previous publication, [27,28,31] Ni-Al-Cr alloys were selected for vaporization examination of their thermodynamic properties for simplicity purposes. To understand the mechanism and minimize the surface defect formation during manufacturing of Ni-base superalloys, we conducted quantitative analysis of elemental vaporization under real industrial processing conditions.…”
Section: Ni-base Superalloys Have Been Developed Formentioning
confidence: 99%